Plant traits and drought tolerance in the savanna : a Kruger National Park case study - Shabane, Tirelo (Department of Biological Sciences, 2017)
One of the central goals of plant ecology is to understand the factors that control the local distribution of plant species and thus the composition of communities. The aim of this study is to determine plant functional traits that can be associated with drought tolerance/avoidance and to test whether wood density is a good indicator of drought tolerance. The study was carried out in Kruger National Park in the month of June. A number of plant traits including wood density, leaf thickness, leaf life span/longevity and water potential were measured along a rainfall gradient (from south to north of the park). Wood density and water potential did not show any significant differences between the wet and dry sites. Leaf thickness and percent leaf cover showed significant correlations with the rainfall gradient (p=0.00 and 0.02 respectively). Wood density may not be the single most important factor that confers fitness during drought. Tolerance in plants may come about as a result of the interplay between plant traits and site characteristics that may result in the differential response even in plants that may be deemed drought tolerant.